The Reality achieving educational and educational goals for school administrations from physical education teachers from the point of view of other disciplines - Abdulzahra, Dhiaa; Khadem, Farqad Abduljabar (Journal of Physical Education, 2022)
The aim of the research is to identify the reality of achieving the educational goals of school administrations in Baghdad. Descriptive research method was adopted on a sample of Boys Middle Schools teachers attributed to six general directorates of education in the province of Baghdad, and continuing teaching for (2021/2022) each according to his specialization. Except for physical education teachers, who are affiliated with mediums run by those who specialize in physical education only in these six directorates, they are numbered (482) individuals which represent (12.274%) of the origin community. The researchers adopted a measure to achieve the educational and educational goals as a scale to survey the opinions, tendencies and trends of the application sample. The researchers verified their results by using the (SPSS) system, in middle schools at various regions in Baghdad, the capital, for the period extending from (1/12/2021) until (28/1/2022). They conclude that middle school The researchers verified that the results were processed using the SPSS system, so that the conclusions and applications of school administrations in the field of physical education at an acceptable level The possibility of achieving educational and educational goals that help achieve educational goals. The level of educational planning ability of school administrations is a specialty of physical education The level of educational planning ability of school administrations is a specialty of physical education to be at an advanced level. This is due to the importance of this type of planning in management. From the point of view of other disciplines. for the faculties of physical education and sports sciences to pay attention to increase sport management lessons or its branches of study materials, that's due to what labor market's needs of these graduates to fill an administrative task within their professional work in the future.